Mandat Yang Terlupakan: Mengaktivasi Kembali Otoritas Spiritual Jemaat Awam Dalam Pelayanan Pelepasan (Sebuah Kajian Teologis) - Haryo Kanigoro Arianto; Tricia Verina Saper (Sekolah Tinggi Teologi Shema Cianjur, 2026)
Deliverance ministry is a crucial dimension of the church's mission; however, in modern ecclesiastical praxis, this role is often narrowed into an exclusive ministry reserved for the clergy or individuals with specific spiritual gifts. This phenomenon has created a